Análise integrativa e sistêmica da redes neuroimunológicas no Transtorno Depressivo Maior (TDM): Estudo da assinatura molecular) - Haroldo Dutra Dias (2024)
Major Depressive Disorder (MDD) is a complex psychiatric condition. Genomic and transcriptomic data of different brain and immune cells have been explored to understand this disorder’s pathophysiology. However, a comprehensive analysis of genomic and transcriptomic data via an integrative systems neuroimmunology approach remains to be performed. This study integrates data from multiple sources, including eligible GWAS meta-analyses identified using PubMed and transcriptomic datasets from the Gene Expression Omnibus (GEO) repository. After differential expression and enrichment analyses, we found clusters enriched by interconnected immune- and nervous-system-related differentially expressed genes (DEGs) from blood and the anterior cingulate cortex samples. While different genes were dysregulated in different MDD cohorts, they often participate in similar biological pathways and processes, underscoring the complex and multifactorial nature of MDD. Furthermore, 31 shared genes between genomic and transcriptomic studies stratified MDD patients from healthy controls, remarkably interconnected DEGs in peripheral blood mononuclear cells (PBMCs). Assessing the probability of developing MDD based on gene expression, NEGR1, PAX6, PPP6G, and SORCS3 emerged as significant genes. A diseasome analysis mapped the broader disease context of these genes, highlighting their multifaceted roles in human health and their potential as nodes in the complex network of genetic factors contributing to MDD and other disorders. This work provides valuable insights into the pathophysiology of MDD and offers a foundation for future research on biomarker development and therapeutic targeting of neuroimmunological pathways in psychiatric disorders